Exploring Perspectives on Antimicrobial Use in Livestock: A Mixed-Methods Study of UK Pig Farmers - Coyne, Lucy A.; Latham, Sophia M.; Dawson, Susan; Donald, Ian J.; Pearson, Richard B.; Smith, Rob F.; Williams, Nicola J.; Pinchbeck, Gina L. (Frontiers in Veterinary Science, 2019)
Increasing levels of antimicrobial resistance in human and veterinary medicine have raised concerns over the irresponsible use of antimicrobials. The role of administering antimicrobials in food producing animals most frequently falls to the farmer, therefore it is essential that their use of antimicrobials is both optimal and responsible. This study sought in-depth information on the drivers behind antimicrobial use behaviours and farmer attitudes to responsible use using a mixed-methodological approach. Initially, in-depth semi-structured interviews were conducted with a purposively selected sample of farmers (n=22). A thematic analysis approach was taken to identify key themes from these qualitative data. The generalisability and variation of these themes was then tested on a larger randomly selected sample of pig farmers through a questionnaire study (n=261). The influences behind antimicrobial use were complex with multiple factors drivingdrivers motivating decisions. There was no consensual opinion on what farming systems resulted in either a low or high antimicrobial requirement however, farmers reported that good management practices, low stocking densities and a high health status were factors associated with low antimicrobial use. Farmers expressed desire to avoid the long-term use of in-feed antimicrobials, but identified barriers to discontinuing such behaviours, such as pig morbidity, mortality and economic losses. The high cost of antimicrobials was described as a motivation towards seeking alternative methods of controlling disease to prophylactic use; however, this expense was balanced against the losses from an increased burden of disease. The high financial costs involved in pig production alongside the economic uncertainty of production and pressure from retailers, were identified as limiting the scope for improvements in pig accommodation and facilities which could reduce the antimicrobial requirements on farm. Long-term, sustainable and economically stable relationships between retailers and farmers may allow farmers to make necessary investments in improving management and housing in order to reduce antimicrobial use. Greater use and more widespread deployment of effective vaccinations were highlighted by farmers as being a feasible alternative to antimicrobial use in preventing disease.